RESEARCH OF WITNESS SAMPLES OF SEAMLESS HOT-ROLLED PIPES AFTER TESTS IN WELLS OF OIL FIELDS OF RUP «ON «BELORUSNEFT» REGARDING THEIR CORROSION RESISTANCE - I. A. Kovaleva; N. A. Hodosovskaya (Литьë и металлургия, 2016)
Field tests of the witness samples of corrosion made of seamless hot-rolled pipes of various steel brands produced by JSC «BMZ – Management Company of Holding «BMK» were carried out in the operating pipelines at three oil fields. The results of the conducted researches made by the experts of RUP «ON «Belorusneft» permitted to define the most stable steel brands against corrosion for each of the oil fields: for a well 146 New and Davydovsky fields – brand steel TT309; for a well 270 Rechitsky fields – steel brands 20 and TT359; for a well 59 Ostashkovichsky fields – TT309 brand steel.